2019
DOI: 10.1111/zph.12624
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiology and genotyping of hepatitis E virus in Singapore reveal rise in number of cases and similarity of human strains to those detected in pig livers

Abstract: Hepatitis E virus (HEV) causes 20 million infections worldwide yearly, of which only about 3.3 million are symptomatic. In developed Asian countries, HEV strains detected in human sera and in food sources were genetically similar, suggesting that indigenous HEV infections may be largely food‐borne. To assess the burden of hepatitis E in Singapore, we performed a seroepidemiologic study of the infection. Additionally, we carried out HEV genotyping on archived, residual HEV IgM‐positive serum samples collected b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…However, in Singapore, the situation was the reverse of what is observed in Cambodia. Here, IgG seroprevalence increased from 14% in 2007 to 35% in 2016 [ 58 ]. In addition to factors enumerated as influencing variation of seroprevalence between countries, cultural practices, eating habits, and whether a country is developed or developing [ 59 ] will affect seroprevalence within a particular country.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in Singapore, the situation was the reverse of what is observed in Cambodia. Here, IgG seroprevalence increased from 14% in 2007 to 35% in 2016 [ 58 ]. In addition to factors enumerated as influencing variation of seroprevalence between countries, cultural practices, eating habits, and whether a country is developed or developing [ 59 ] will affect seroprevalence within a particular country.…”
Section: Discussionmentioning
confidence: 99%
“…However, even in Singapore, a developed country with a high – income economy, the seroprevalence (of 10.5% – 22.3%) appeared relatively high [ 58 , 60 ]. This scenario goes to prove that the endemicity of HEV is no longer restricted to only developing countries, but even developed countries are no exception [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Singapore, hepatitis E is listed as one of the infectious diseases notifiable to the Ministry of Health. In recent years, there have been reports of increased hepatitis E incidence and increased HEV seroprevalence rates among immunocompromised individuals (Tan et al., 2013; Wong et al., 2019; Zhu et al., 2019). These studies hypothesized a possible food‐borne route of HEV infection in Singapore as the local cultural predilection among the non‐Muslim population is to eat pig liver semi‐cooked.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, examining the prevalence of HEV in slaughterhouse pigs will provide an indication of its occurrence in the regional source farm. Additionally, a recent study by Wong et al (2019) had demonstrated the presence of G3 HEV in pig livers sold at local markets. Therefore, the aim of this study was to investigate the presence of HEV further upstream along the food supply chain through an examination of anti-HEV antibodies and HEV RNA in imported pig samples and post-slaughter livers collected from 2000 to 2019.…”
Section: Introductionmentioning
confidence: 99%